Invasive clams (Ruditapes philippinarum) are better equipped to deal with harmful algal blooms toxins than native species (R. decussatus): evidence of species-specific toxicokinetics and DNA vulnerability - Braga, Ana C. (2021)
This study aims to assess and compare the kinetics (accumulation/elimination) of the marine biotoxins okadaic acid (OA) and dinophysistoxin-1 (DTX1 ), between native (Ruditapes decussates) and invasive (Ruditapes philippinarum) clam species, and their genotoxic effects and DNA recover capacity after, exposure to toxic dinoflagellates Promcentrum lima. Clams were fed with P. lima for 5 days and then to non-toxic algae (post-exposure) during other 5 days. Toxin concentrations determined in clams by LC-MS/MS were related with DNA damage and repair assessment through the comet and base excision repair (BER) assays, respectively. Differential accumulation patterns were observed between the invasive and native species. The invasive species consistently and progressively accumulated the toxins during the first 24 h of exposure, while the native clams showed drastic variations in the toxin accumulation. Nevertheless, at the end of a 5 days of exposure period, the native dams presented higher toxin concentrations, nearly reaching the legal regulatory limit for human consumption. In addition, native clams were vastly affected by OA and DTX1, presenting an increment in the DNA damage since the first day, with a correspondent increase in the repair activity. On the other hand, invasive clams were not affected by the dinoflagellate toxins, exhibiting only some signs of the challenge, namely an increase in the DNA repair mechanisms in the post-exposure period. Invasive clams R. philippinanim are better adapted to cope with harmful algal blooms and OA-group toxins than native species. These results may increase farming interest and may lead to new introductions of the invasive clams. In sympatry sites, exposure to OA-group toxins may unbalance dams species biomass and distribution as exposure to toxic dinoflagellates affects the native clams from cellular to a population level, representing a significant threat to development and maintenance of R. decussates populations. (C) 2021 Elsevier B.V. All rights reserved.